EXQ: measurement of healthcare experience quality in Malaysian settings: A contextualist perspective. Issue 1 (4th April 2016) - Kashif, Muhammad; Samsi, Siti Zakiah Melatu; Awang, Zainudin; Mohamad, Mahadzirah
Abstract : Purpose: – The customer experience quality (EXQ) cannot be measured by using traditional tools to investigate service quality. There is a need to use new tools to directly measure EXQ from a customer perspective. The current study aims to contribute in this domain of knowledge and validate EXQ scale by linking it to marketing outcomes of satisfaction, loyalty and word of mouth in Malaysian private healthcare settings. Design/methodology/approach: – The authors collected data from 330 randomly selected Malaysians, visiting private hospitals in the city of Kuala Lumpur. The data analysis is performed by confirmatory factor analysis using structural equation modelling – SEM – procedures. Findings: – The results reveal that two dimensions of EXQ scale moments of truth and peace of mind are highly valued by customers. Furthermore, the EXQ perceptions significantly contribute to satisfaction and loyalty. In a mediating relationship, the customer satisfaction is found to be a positive and significant variable. Practical implications: – Healthcare marketing policymakers should emphasize on recruitment of frontline staff – individuals with strong interpersonal skills and expertise who are able to create a memorable customer service experience. Originality/value: – The study is an original contribution to the existing body of knowledge – generally in services marketing literature and specifically in the field of healthcare marketing with a focus on customer experience in a developing country context of Malaysia.